Analysis of Factors Affecting Low Measles Rubella Immunization Coverage During School Children Immunization Month in Elementary Schools in Center Area, Padang - Suilia, Rania; Meri Neherta; Agus Sri Banowo; Rika Sabri; Mahathir; Fitra Yeni (NERS Jurnal Keperawatan, 2026)
Measles Rubella (MR) immunization is a vaccine aimed at preventing measles and rubella. MR are infectious diseases that can affect anyone, both children and young adults, and can cause serious health problems. These diseases can lead to severe complications such as pneumonia, encephalitis, congenital defects, and even death. Despite being an effective preventive measure, MR immunization coverage has shown a significant decline in recent years, from 88% in 2022 to only 42.4% in 2024. In Padang City, the MR immunization coverage among grade 1 students in 2024 were only 33.1%, far below the national target of 90%. This study aimed to analyze the factors influencing the low coverage of MR immunization in Padang City. This research employed a quantitative approach with a cross-sectional design. The total sample consisted of 136 respondents, specifically mothers who have children enrolled in grade 1 of elementary school. The sampling technique used was simple random sampling. Data were collected through structured questionnaires and analyzed using chi-square statistical tests to identify relationships between variables. The results indicated a significant relationship between attitude, belief, and family support with MR immunization coverage. In contrast, there was no significant relationship between knowledge, health worker support, and community leader support. Among all analyzed variables, belief (22.962), family support (5.606), and attitude (7.148) had the strongest influence on immunization coverage. Therefore, it is recommended that the Health Office and Nanggalo Health Center enhance targeted health promotion strategies and community engagement to improve Measles Rubella immunization coverage.